Time Prediction of Dynamic Behavior of Glass Fiber Reinforced Polyester Composites Subjected to Fluctuating Varied Temperatures - Yousuf, Louay S. (Al-Khwarizmi Engineering Journal, 2009)
The reduction of vibration properties for composite material (woven roving E-glass fiber plies in thermosetting polyester matrix) is investigated at the prediction time under varied combined temperatures (60 to -15) using three types of boundary conditions like (CFCF, CCCF, and CFCC). The vibration properties are the amplitude, natural frequency, dynamic elastic moduli (young modulus in x, y directions and shear modulus in 1, 2 plane) and damping factor. The natural frequency of a system is a function of its elastic properties, dimensions, and mass. The woven roving glass fiber has been especially engineered for polymer reinforcement; but the unsaturated thermosetting polyester is widely used, offering a good balance of vibration properties at moderate or ambient temperatures, and also at relatively low cost. The mismatch between matrix and fiber yarns gives a predominant role for the fiber’s mechanics where the matrix is the area where most damage mechanisms develop. The free vibration test was carried out for (5, 10, 15, 20, 25, 30) minutes. The composite plate was exposed to (75) of thermal gradient for ten times in various times at different stages. The results were classified into experimental and finite element using software ANSYS Ver. 9.